Leaching resistance of alkali-activated slag and fly ash mortars exposed to organic acid. Issue 3 (1st August 2018) - Li, Zihui; Peethamparan, Sulapha
Abstract : This paper presents a comprehensive evaluation of the leaching resistance of alkali-activated mortar (AAM) in an organic, acetic acid environment in comparison with ordinary Portland cement (OPC) mortars. Two AAMs, a ground granulated blast-furnace slag mortar and a class C fly-ash-based mortar, and two OPC mortars were exposed to pH = 3·2 and pH = 4·0 acetic acid solutions for 90 d. Residual compressive strength and mass changes were determined periodically to quantify the degree of degradation caused by the organic acid exposure. Additionally, a microstructural investigation of the degradation was performed using scanning electron microscopy and energy-dispersive X-ray spectroscopy in order to identify the occurrence of microscale damage after acid exposure. The leachates were analyzed at various soaking periods using inductively coupled plasma mass spectrometry to determine the concentration of the leached calcium (Ca), silicon (Si), aluminum (Al), sodium (Na), sulfur (S) and other related ions. The AAM samples exhibited enhanced leaching resistance compared to traditional OPC mortars.